Rapid Discrimination of Chlorpheniramine Maleate and Assessment of Its Surface Content Uniformity in a Pharmaceutical Formulation by NIR-CI Coupled with Statistical Measurement - Luwei Zhou; Zhisheng Wu; Xinyuan Shi; Manfei Xu; Xiaona Liu; Bing Xu; Yanjiang Qiao (Journal of Spectroscopy)
This study demonstrated that near infrared chemical imaging (NIR-CI) was a rapid and nondestructive technique for discrimination of chlorpheniramine maleate (CPM) and assessment of its surface content uniformity (SCU) in a pharmaceutical formulation. The characteristic wavenumber method was used for discriminating CPM distribution on the tablet surface. To assess the surface content uniformity of CPM, binary image and statistical measurement were proposed. Furthermore, high-performance liquid chromatography (HPLC) was used as reference method for accurately determining volume content of CPM in the sample. Moreover, HPLC was performed to assess volume content uniformity (VCU) of CPM in whole region and part region of the tablets. The NIR-CI result showed that the spatial distribution of CPM was heterogeneous on the tablet surface. Through the comparison of content uniformity of CPM determined by NIR-CI and HPLC, respectively, it demonstrated that a high degree of VCU did not imply a high degree of SCU of the samples. These results indicate that HPLC method is not suitable for testing SCU, and this has been verified by NIR-CI. This study proves the feasibility of NIR-CI for rapid discrimination of CPM and assessment of its SCU, which is helpful for the quality control of commercial CPM tablets.